Analisis Kesantunan Berbahasa Pada Buku Bahasa Indonesia 2 Sma Kelas XI Penerbit Quadra Karangan Sri Sutarni Dan Sukardi - Kusuma, Dhimas Widya (2016)
The system has the function of language as a means of ongoing human interaction in society. Politeness principle is one of the principles in the study of interpersonal rhetoric. This study aimed to analyze the politeness in Indonesian Book 2 High School Class XI Publisher Quadra Authorship Sri Sutarmi and Sukardi and identify deviations politeness in Indonesian Book 2 High School Class XI Publisher Quadra Authorship Sri Sutarmi and Sukardi. This study is descriptive qualitative research. Research on politeness on these held in Surakarta by taking Indonesian Book 2 High School Class XI Publisher Quadra bouquet Sri Sutami and Sukardi in Bogor. The implementation of the time the study began in November to December 2015. The method used in this research is the frontier intralingual. The results showed that there are 30 discourses are included in the principle of politeness that is the maxim of wisdom, generosity, acceptance, humility, suitability and attention. The use of the principle of modesty in textbooks is necessary, as it will give a speech act politeness towards students. Irregularities and abuses the principle of courtesy on the Indonesian Book 2 High School Class XI Publisher Quadra Authorship Sri Sutarmi and Sukardi, which, in the maxim of wisdom, generosity, acceptance, humility, suitability and attention.